2021
DOI: 10.1186/s12958-021-00815-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in helicase for meiosis 1 lead to male infertility due to non-obstructive azoospermia

Abstract: Background Non-obstructive azoospermia (NOA) is the most severe form of male infertility; more than half of the NOA patients are idiopathic. Although many NOA risk genes have been detected, the genetic factors for NOA in majority of the patients are unknown. In addition, it is difficult to retrieve sperm from these patients despite using the microsurgical testicular sperm extraction (microTESE) method. Therefore, we conducted this genetic study to identify the potential genetic factors responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Although these patients underwent micro-TESE, no spermatozoa were retrieved in the testes (Ref. 55). In another study, we found that SSR was achieved by micro-TESE in a patient with INOA bearing a variant of the DMRT1 (OMIM: 602424) gene (Ref.…”
Section: Dnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these patients underwent micro-TESE, no spermatozoa were retrieved in the testes (Ref. 55). In another study, we found that SSR was achieved by micro-TESE in a patient with INOA bearing a variant of the DMRT1 (OMIM: 602424) gene (Ref.…”
Section: Dnasmentioning
confidence: 99%
“…50) and TEX14 (OMIM: 605792) (Refs 51, 52). In parallel, several researchers explored the association between precise genetic diagnosis and SSR by micro-TESE in patients with INOA, aiming to propose genetic predictors for SSR prior to surgery (Refs 50, 5355).…”
Section: Dnasmentioning
confidence: 99%
“…Nonobstructive azoospermia (NOA) is a serious male infertility disorder that accounts for more than 20% of the male infertility issues (Cioppi et al, 2021). NOA is typically associated with genetic defects, including Y chromosome microdeletions and spermatogenesis related gene mutations (TEX11, HFM1, and MEI1) (Yatsenko et al, 2015;Ben Khelifa et al, 2018;Tang et al, 2021). The causes of female infertility include premature ovarian insufficiency (POI), abnormal ovulation, tubal blockage and endometriosis (Sen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…POI is characterized by loss of normal ovarian function in women before 40 years of age (De Vos et al, 2010). It has been reported that a number of genes are responsible for POI, such as DNA damage repair relevant genes (FANCA, DMC1, MCM8, etc) (Desai et al, 2017;He et al, 2018;Yang et al, 2019) and hormone receptor genes (FSHR, LHCGR, etc) (He et al, 2019;Guo et al, 2021;Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation is one of the important causes of male infertility. Recently, Tang et al [ 2 ] reported that variants of homozygous helicase for meiosis 1 are responsible for spermatogenic failure. MLH3 single nucleotide polymorphisms in human populations can lead to male infertility [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%